The perception of UiTM B. Ed. TESL students on the effects of microteaching towards their practicum / Izzatul Sahanah Ja'afar - Ja'afar, Izzatul Sahanah (Faculty of Education, 2011)
Microteaching is taught as part of methodological subjects to B. Ed. TESL students in the Faculty of Education in UiTM. It is a compulsory subject in the teacher training courses to prepare the students for their practicum in the final year. Despite the usefulness of microteaching, some students experienced teaching failures in their practicum. Hence, this study was conducted among selected number of final year B. Ed. TESL students to investigate to what extent this problem is contributable to microteaching. This is a quantitative and qualitative study, which utilized a 34-item questionnaire, adapted from Ogeyik (2009) as the method of data collection involving 70 students. The purposes of this study are to identify the students’ perceptions on the effects of microteaching on their practicum and suggestions to improve microteaching. In order to measure students’ perceptions on microteaching, four dimensions were used as measurements: motivation, competence, peer group and feedback. In addition, the study investigates gender, CGPA and semester differences with regard to students’ perceptions of microteaching by using t-test and ANOVA. The main findings of this study revealed that the students perceived the effects of microteaching towards their practicum positively. It was also found that there were significant differences of perceptions on microteaching effects towards their practicum according to genders and semesters in terms of competence. A number of suggestions were also proposed for further consideration. It is hoped that this study will give insights to the faculty to enhance microteaching in teacher training courses in the hopes of creating new well-bred teachers.